STUDY ON THE ASH COMPOSITION OF Albazia Falcataria - Bahri, Mokhammad Hairul (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v6i1.1191, 2015)
Search environmentally energy sources to reduce the impact of global warming is being done. The Government of Indonesia through SMRTI 2006 was developing and implementing science and technology fields of new and renewable sources of energy to support the security of energy supply in 2025 for the next of human survival. Biomass is a one of  renewable energy. In this research,  Sawdust Of Albazia Falcataria as solid fuel was investigated using SEM-EDAX  to  know the composition for preventing damage in heat exchanger. Problems in heat exchanger are slagging and fouling caused by biomass burning. The investigation of Albizia Falcataria were contains S, K before burning 0,27%, 0,56% and  0,49%, 0,82% for ash respectively. By using biomass energy as solid fuel decreased usage of fossil fuel to diminish global warming effect and sustainaibilty of the earthlife.